Implementasi Metode Prototype Dalam Perancangan E-Commerce Sebagai Platform Jual Beli Produk Power Cleanser - Fiqri Adiperdana; Yulianti (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Power cleaner is a homemade product where this power cleaner aims to clean areas that are difficult to clean, previously this power cleaner product has been marketed through door to door only with a very small scope and also with the existence of marketplaces such as shopee, tokopedia that encourage this cleaning power product to marketed through e-commerce, but with the policy of the Indonesian government on increasing taxes, it greatly affects the turnover and price of the power cleaner product which makes purchasing power weak, which is where the admin costs of the buying and selling process on e-commerce are relatively high. In this study, data collection was carried out in several stages starting from literature study, field study using observation, interviews, and similar literature studies. The development methodology used in the manufacture of this system is prototype development. And tested using the blackbox test method and a questionnaire. After revealing and knowing the system that is running, the proposed problem solver on the system will be made an e-commerce application design system for power cleaner products that can assist in managing data on products sold. Based on the results of implementation and testing, it can be concluded that the implementation of the prototype method in the design of e-commerce as a buying and selling platform for power cleaner products greatly increases productivity and independence in entrepreneurship in order to create a product that has high purchasing power and is known to the wider community.